Assessing the Kiken Yochi Training (KYT) in Improving Osh Awareness and Behavior among Workers at HPI Perak - Nurul Sharmimi Binti Ahmad Sharifuddin; Pravina Delagannu (Progress in Engineering Application and Technology, 2026)
Workers in manufacturing industries frequently face various workplace hazards, including the operation of machinery, manual handling tasks, and exposure to dust and chemicals, making safety and health management critically important. Proactive safety training is essential to strengthen hazard awareness and promote safe work practices. Despite ongoing safety initiatives, workplace accident rates in the manufacturing sector remain high. This situation indicates a need for proactive safety training such as Kiken Yochi Training (KYT) to improve workers hazard awareness and encourage safer work behavior. This study aims to assess the level of OSH awareness and evaluate the impact of KYT on safety behavior among workers at HPI Perak. A quantitative cross-sectional study was conducted using a structured questionnaire based on a standardized KYT evaluation form provided by the company. Stratified sampling was applied to select workers from the Printing and Finishing Departments. Data were analyzed using descriptive statistics, including frequency, percentage, and mean scores. The findings revealed high mean scores for both OSH awareness and safety behavior, indicating that KYT effectively enhanced workers understanding of workplace hazards, encouraged positive safety attitudes, and improved safe work practices. Continuous and structured implementation of KYT is recommended to sustain safety awareness and behavior. Greater worker participation and periodic updates of KYT content are suggested to further strengthen its effectiveness in manufacturing environments.